2004
DOI: 10.1177/104063870401600518
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Adenovirus and an Adeno-Associated Virus from Goat Kids with Enteritis

Abstract: Abstract.A dairy goat operation in Minnesota experienced a sudden, markedly increased mortality among its neonatal goats. Approximately 60 of 130 kids (46%) died. The animals had diarrhea and dyspnea of 1-2 days duration before death. Necropsy of 4 goat kids revealed marked, acute, catarrhal enteritis and fibrinous pleuropneumonia. Mannheimia haemolytica was isolated from the lungs. Basophilic inclusion bodies filling the entire nucleus were present in enterocytes of the ileum of 3 goats. Adenoviral particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Four adenovirus preparations derived from a pool of postmortem ileum samples from four young goats concurrently afflicted with viral catarrhal enteritis and bacterial fibrinous pleuropneumonia (29) were received from the National Animal Disease Center (Ames, IA) for AAV screening. The four adenovirus preparations shared the same inoculum but were propagated using different host cells (ovine turbinate cells, primary lamb kidney cells, or Madin-Darby bovine kidney cells).…”
Section: Resultsmentioning
confidence: 99%
“…Four adenovirus preparations derived from a pool of postmortem ileum samples from four young goats concurrently afflicted with viral catarrhal enteritis and bacterial fibrinous pleuropneumonia (29) were received from the National Animal Disease Center (Ames, IA) for AAV screening. The four adenovirus preparations shared the same inoculum but were propagated using different host cells (ovine turbinate cells, primary lamb kidney cells, or Madin-Darby bovine kidney cells).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to human and primates, AAV has also been isolated from different species including cow [Schmidt, M et al, 2004], chicken [Bossis. I and Chiorini, JA, 2003], sheep [Clarke, JK et al, 1979], snake [Farkas, SL et al, 2004], lizard [Jacobson, ER et al, 1996], and goat [Olson, EJ et al, 2004]. The isolation of new AAV serotypes from animal tissues and the development of these new variants into gene therapy vectors are discussed in a separate review in this issue [Gao et al].…”
Section: Isolation Of Aav Serotypes From Animal Tissues: Aav1 -11mentioning
confidence: 99%
“…AAV has been isolated from many organisms including human, nonhuman primates, ovine, avian, snake, bovine, murine and caprine. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] It has been reported that various AAV serotypes have differing tropisms and can transduce specific organs more efficiently than others, such as the high transduction efficiency of AAV5 in airway epithelial, muscle and retina cells as compared to AAV2. 15,16 Gene transfer vectors derived from AAV can deliver genes in a variety of tissues in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In the past, AAV has conventionally been isolated from contaminated adenoviral stocks or young, sick animals or children. [1][2][3][4][5][6][7]9,12 Recently, isolation of new AAV isolates was extensively performed using PCR amplification of AAV sequences from genomic DNA of different animal species. 8,10,11,13 In this study, novel porcine AAV sequences were identified by PCR using genome walking strategies.…”
Section: Introductionmentioning
confidence: 99%